Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Hoàng Văn Hưng
Xem chi tiết
Nguyễn Minh Hiệu
Xem chi tiết
Cold Wind
11 tháng 9 2016 lúc 10:17

\(5x^2y^2+20x^2y-35xy^2\)

\(=5xy\left(4x-7y\right)\)

\(x+1-x^2+54+x^3\)

Mịnh Quân
22 tháng 9 2016 lúc 20:06

a = 5x(xy+4x-7y

Nguyễn tấn dũng
Xem chi tiết
Nguyễn Ngọc Tho
27 tháng 12 2017 lúc 20:19

x6y - 5x- 4x4y + 20x3 

= ( x6y - 5x5 ) - ( 4x4y - 20x3 ) 

= x5( xy - 5 ) - 4x3( xy - 5 )

= ( x5 - 4x3 )( xy - 5 ) = x3( x2 - 4 )( xy - 5 ) 

= x3( x - 2 )(x + 2 )( xy - 5 )

Nguyễn Anh Quân
27 tháng 12 2017 lúc 20:15

 = x^3.(x^3y-5x^2-4xy+20)

 = x^3.[(x^3y-5x^2)-(4xy-20)]

 = x^3.(y-5).(x^2-4) = x^3.(x-2).(x+2).(y-5)

k mk nha

Trần Nam Khánh
Xem chi tiết
Nguyễn Lê Phước Thịnh
10 tháng 9 2021 lúc 0:18

a: Ta có: \(-3x^4+20x^3-35x^2-10x+48\)

\(=-\left(3x^4-20x^3+35x^2+10x-48\right)\)

\(=-\left(3x^4-9x^3-11x^3+33x^2+2x^2-6x+16x-48\right)\)

\(=-\left(x-3\right)\left(3x^3-11x^2+2x+16\right)\)

\(=-\left(x-3\right)\left(3x^3-6x^2-5x^2+10x-8x+16\right)\)

\(=-\left(x-3\right)\left(x-2\right)\left(3x^2-5x-8\right)\)

\(=-\left(x-3\right)\left(x-2\right)\left(3x-8\right)\left(x+1\right)\)

b: Ta có: \(-\left(2x^4+7x^3+x^2-7x-3\right)\)

\(=-\left(2x^4-2x^3+9x^3-9x^2+10x^2-10x+3x-3\right)\)

\(=-\left(x-1\right)\left(2x^3+9x^2+10x+3\right)\)

\(=-\left(x-1\right)\left(2x^3+2x^2+7x^2+7x+3x+3\right)\)

\(=-\left(x-1\right)\left(x+1\right)\left(2x^2+7x+3\right)\)

\(=-\left(x-1\right)\left(x+1\right)\cdot\left(x+3\right)\left(2x+1\right)\)

tùng rùa
Xem chi tiết
Lấp La Lấp Lánh
17 tháng 10 2021 lúc 13:50

\(x^4+x^3-20x^2-47x-15\)

\(=x^3\left(x-5\right)+6x^2\left(x-5\right)+10x\left(x-5\right)+3\left(x-5\right)\)

\(=\left(x-5\right)\left(x^3+6x^2+10x+3\right)\)

\(=\left(x-5\right)\left[x^2\left(x+3\right)+3x\left(x+3\right)+\left(x+3\right)\right]\)

\(=\left(x-5\right)\left(x+3\right)\left(x^2+3x+1\right)\)

Nguyễn Hoàng Minh
17 tháng 10 2021 lúc 13:51

\(=x^4-5x^3+6x^3-30x^2+10x^2-50x+3x-15\\ =\left(x-5\right)\left(x^3+6x^2+10x+3\right)\\ =\left(x-5\right)\left(x^3+3x^2+3x^2+9x+x+3\right)\\ =\left(x-5\right)\left(x+3\right)\left(x^2+3x+1\right)\)

Minh Lâm
Xem chi tiết
Nguyễn Lê Phước Thịnh
24 tháng 12 2021 lúc 19:10

\(=4xy\left(1-5x^2y+4xy\right)\)

Đỗ Vũ Hoàng Anh
24 tháng 12 2021 lúc 19:14

=4xy(1-  5x2y+4xy) 

Lihnn_xj
24 tháng 12 2021 lúc 19:16

= 4xy ( 1 - 20x2y + 4xy )

Hai Hien
Xem chi tiết
nthv_.
27 tháng 9 2021 lúc 20:35

a. (2x - 5)2

b. x(x2 - 1) = x(x - 1)(x + 1)

c. (x - 3)(x2 + 3x + 9)

d. 5x(x - y) + (x - y) = (x - y)(5x + 1)

Hà Phạm
Xem chi tiết
Nguyễn Lê Phước Thịnh
20 tháng 10 2021 lúc 23:17

\(5\left(x^2+y^2\right)^2-20x^2y^2\)

\(=5x^4+5y^4-10x^2y^2\)

\(=5\left(x^2-y^2\right)^2\)

\(=5\left(x-y\right)^2\cdot\left(x+y\right)^2\)

Akai Haruma
20 tháng 10 2021 lúc 23:34

Lời giải:

$5(x^2+-y^2)^2-20x^2y^2=5(x^2-y^2)^2-20x^2y^2$

$=5[(x^2-y^2)^2-(2xy)^2]=5(x^2-y^2-2xy)(x^2-y^2+2xy)$

 

Nguyễn Thị Mỹ Trúc
Xem chi tiết
Kiều Vũ Linh
1 tháng 11 2023 lúc 10:25

5²y² + 10xy³ - 20xy²

= 5y.(5y + 2xy² - 4xy)